ИНТЕРНЕТ ТИЗИМИДА ИНГЛИЗ ТИЛИНИНГ ЎЗИГА ҲОС ХУСУСИЯТЛАРИ.(АВСТРАЛИЯ ВАРИАНТ МИСОЛИДА) - Imamamliyev, Zuhriddin (Журнал иностранных языков и лингвистики, 2021)
In addition to the American English and British English forms we know, the article discusses the evolution of the Australian English language and where examples of this type can be found.